Characteristics and Experiences of Employees who Gamble at Work: A Mixed-Methods Study - Hudson Breen, Rebecca; O'Brien, Daniel; Sanders, James (Critical Gambling Studies, 2024)
Given that little is currently known about gambling in the workplace, we conducted a mixed-methods study to describe the characteristics and experiences of people who gamble at work. We administered a Canada-wide online survey (n = 2,000) of adults who 1) gamble, 2) are currently employed full-time, and 3) have internet access at work. A descriptive analysis of quantitative survey data showed that individuals who gamble at work had lower job satisfaction and higher rates of problem gambling compared to those who do not. Among those who gamble at work, we quantitatively described the types of gambling, the consequences experienced, and the motivations for gambling. Qualitative interviews were conducted with 18 individuals who met the criteria for problem gambling and who gamble at work. Data were integrated to provide a richer description of the experiences of those who gamble at work, including their motivations, the role of work–life satisfaction, and the dynamic influence of work as a social context. Motivations for workplace gambling included excitement, social connection, avoidance, and coping with stress or emotions. The results highlight the importance of understanding the varied motivations of individuals who gamble at work, and the role of work experiences in shaping meaning regarding gambling behaviours.